Դերենիկ Դեմիրճեանի երգիծանկարները - Ռաֆայէլեան, Կարինէ (տպ. Atlas)
The archival legacy of the renowned Armenian novelist Derenik Demirchian is full of samples of diverse unpublished documents. These include not only his literary works but also the drawings he made during his lifetime. The current article highlights Demirchian’s hitherto unpublished eleven pencil drawings, which are caricatures. Most of these caricatures are done on separate papers, while others are drawn either on the manuscript pages or the letters of the author. Almost all the drawings have write-ups by Demirchian, which sound more like comments and explanations. In fact, Demirchian was not only caricaturing but also expressing his views and attitude towards the figures he was drawing. Furthermore, these comments, about the renowned figures he was drawing, reflect as well events of the time. The set of caricatures published in this article belong to Hovhannes Toumanian, Leo, Berdj Broshian, Alexander Dzadourian, Hovhannes Aivazovsky, and the most famous Armenian periodicals of the time, specifically Mourdj (hammer) and Meshag (peasant, cultivator) These eleven caricatures shed light on Demirchian’s drawing talent and his literary and socio-political position concerning a number of critical issues of the time. It helps us to see Demirchian from a different, unexamined perspective and to recognise how deep and piercing a multitalented personality he was. In this regard, Demirchian is a rare case as very few Armenian writers have been able to produce wonderful literary works (the Vartanank novel in his case) as well as shine with other talents.
Keywords: Երգիծական գրականութիւն; Ծաղրանկարչութիւն